Flecainide-Induced Brugada Syndrome in a Patient With Skeletal Muscle Sodium Channelopathy: A Case Report With Critical Therapeutical Implications and Review of the Literature - Cavalli, Michele; Fossati, Barbara; Vitale, Raffaele; Brigonzi, Elisa; Ricigliano, Vito A. G.; Saraceno, Lorenzo; Cardani, Rosanna; Pappone, Carlo; Meola, Giovanni (Frontiers in Neurology, 2018)
Skeletal muscle sodium channelopathies are a group of neuromuscular disorders associated with mutations in the SCN4A gene. Because principal sodium channel isoforms expressed in the skeletal muscles and the heart are distinct one from the other, this condition usually spares cardiac functioning. Nonetheless, evidence on a possible link between skeletal muscle and cardiac sodium channelopathies has emerged in recent years. To date, eight patients bearing pathogenetic mutations in the SCN4A gene and manifesting cardiac electrophysiological alterations have been reported in literature. Among these patients, three presented a phenotype compatible with Brugada syndrome. We report the case of a 29-year-old patient affected by non-dystrophic myotonia associated with a p.G1306E mutation in the SCN4A gene, who presented symptoms of syncope and palpitation after the introduction of flecainide as an anti-myotonic agent. ECG and ajmaline challenge were consistent with the diagnosis of Brugada syndrome, leading to the implantation of a cardioverter defibrillator. No mutation in causative genes for Brugada syndrome was detected. Mexiletine treatment reduced myotonia without any cardiac adverse events. This case report highlights the clinical relevance of the recognition of cardiac electrophysiological alterations in skeletal muscle sodium channelopathies. The discovery of a possible pathogenetic linkage between skeletal muscle and cardiac sodium channelopathies may havesignificant implications in patients’management, also in light of the fact that class 1C anti-arrhythmics are potential triggers for life-threatening arrhythmias in patients with Brugada syndrome.